2018
DOI: 10.1016/j.cgh.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

New Indications for Endoscopic Radiofrequency Ablation

Abstract: Radiofrequency ablation (RFA) is a well-established treatment for several benign, premalignant, and malignant disorders. Although the role of RFA has been clearly defined, new indications for luminal and extraluminal applications of endoscopic RFA-directed therapies have emerged. RFA has recently produced promising results in patients with a variety of gastrointestinal and hepatopancreatobiliary pathologies. For example, endoscopic RFA has been used to treat patients with gastric antral vascular ectasia, chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 76 publications
(103 reference statements)
0
20
0
Order By: Relevance
“…EUS-RFA has been developed to try to ensure a better controlled EUS-guided antitumor treatment combining both tumor necrosis and enhancement of the immune response [20 -22]. A recent review of endoscopic RFA reported only early data on EUS-guided RFA in pancreatic tumors and the largest study included only eight patients [20,22]. They concluded that more data about safety, long-term durability, and clinical indications were needed [20].…”
Section: Discussionmentioning
confidence: 99%
“…EUS-RFA has been developed to try to ensure a better controlled EUS-guided antitumor treatment combining both tumor necrosis and enhancement of the immune response [20 -22]. A recent review of endoscopic RFA reported only early data on EUS-guided RFA in pancreatic tumors and the largest study included only eight patients [20,22]. They concluded that more data about safety, long-term durability, and clinical indications were needed [20].…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) provides a potentially safer alternative to the high rate of complications associated with APC for treatment of CRP. Since the advent of RFA for treatment of Barrett's esophagus, the modality's indications have evolved and expanded to include treatment of variety of gastrointestinal and hepatopancreatobiliary pathologies . While RFA has been increasing utilized for a variety of these conditions, there remains a paucity of data evaluating the safety and effectiveness of RFA for the treatment of CRP …”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of RFA for treatment of Barrett's esophagus, the modality's indications have evolved and expanded to include treatment of variety of gastrointestinal and hepatopancreatobiliary pathologies. 14 While RFA has been increasing utilized for a variety of these conditions, there remains a paucity of data evaluating the safety and effectiveness of RFA for the treatment of CRP. 15 The primary aim of this study was to perform a systematic review and meta-analysis to evaluate the efficacy and safety of RFA for the treatment of CRP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, combination with local therapies has been attempted to improve patients’ survival and quality of life. Radiofrequency ablation (RFA) is a local ablative therapy using heat that leads to coagulative necrosis and local tumor destruction 2,3 . We describe a case of percutaneous endobiliary RFA for recurring bile duct cancer after surgery causing metal stent obstruction.…”
Section: Brief Explanationmentioning
confidence: 99%